Odpowiedzi

Najlepsza Odpowiedź!
2010-01-10T17:01:52+01:00
C) x-2y =3
-2x+y = 0

x=3+2y
-2(3+2y)+y = 0

x=3+2y
-6-4y+y = 0

x=3+2y
-3y =6 /:(-3) (tu był błąd w Twoim rozumowaniu)

y=-2
x=3+2*(-2)

y=-2
x=3-4

y=-2
x=-1
1 5 1
2010-01-10T17:15:40+01:00
X-2y=3
-2x+y=0

x=3+2y
-2(3+2y)+y=0

x=3+2y
-6-4y-y=0

x=3+2y
-3y=6/: (-3)

x=3+2y
y=-2

x=3-4
y= -2

x=-1
y=-2

Mam nadzieje że bd dobrze :)

2010-01-10T19:08:56+01:00
X-2y =3
-2x+y = 0

x=3+2y
-2(3+2y)+y = 0

x=3+2y
-6-4y+y = 0

x=3+2y
-3y =6 /:(-3)

x=3+2y
y=-2

x=3+2*(-2)
y=-2


x=3-4
y=-2

x=-1
y=-2

POZDRAWIAM :)))